Sliding Mode Control of an Isolated Inverter Based on Active Clamped Flyback-Forward Converter - Bagheri, Farzaneh; Bayhan, Sertac; Komurcugil, Hasan (IEEE, 2021)
This paper presents a super twisting sliding mode control method for a high-efficiency high-boost interleaved soft-switching flyback-forward converter supplying a standalone inverter. In the proposed control method, the dc side input current and the ac side load voltage are injected to the sliding mode control as the state variables and the chattering is eliminated by applying the super twisting sliding mode control input. Two main switches and two active clamp switches are leveraged in the dc side which is operated by the signals obtained from the dc side sliding function. The full bridge inverter is controlled by the pulses obtained from the ac side sliding control input. To generate the dc side input current reference, a PI regulator is employed to process the dc side output voltage and determine the input current reference. The simulation results validate the proficiency of the method in terms of zero steady state error, fast time response and robustness against disturbances while achieving a sinusoidal output voltage with low total harmonic distortion.
30th IEEE International Symposium on Industrial Electronics (ISIE) -- JUN 20-23, 2021 -- Kyoto, JAPAN
Keywords: Active clamped flyback-forward converter; super twisting sliding mode control